1984
DOI: 10.2307/3586690
|View full text |Cite
|
Sign up to set email alerts
|

What Really Matters in Second Language Learning for Academic Achievement?

Abstract: This retrospective analysis seeks to explain why a group of children who had been matched for English proficiency and socioeconomic status (SES) when they started a school year, and who were subsequently taught and tested through the medium of English, differed in their school achievement at the end of that year. Factors considered include relative productive competence in English morphology, syntax, and vocabulary; verbosity; patterns of social interaction; first language performance; and personality factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(95 citation statements)
references
References 7 publications
7
83
0
5
Order By: Relevance
“…Conversations in students' homes in a first and/or second language have been shown to support the learning of a new language (Delgado-Gaitan, 1990; Pease-Alvarez, 1993). In fact, heritage-language proficiency and skills have been shown to facilitate English language and literacy generally (Hakuta & Gould, 1987;Saville-Troike, 1984;Troike, 1981). Yet, most teachers fail to capitalize on this in school, and may even counteract the educational benefits of heritage languages by discouraging students from using their first language and by neglecting to foster natural conversations in a first or second language in the classroom.…”
Section: Engaging In Natural Conversationsmentioning
confidence: 99%
“…Conversations in students' homes in a first and/or second language have been shown to support the learning of a new language (Delgado-Gaitan, 1990; Pease-Alvarez, 1993). In fact, heritage-language proficiency and skills have been shown to facilitate English language and literacy generally (Hakuta & Gould, 1987;Saville-Troike, 1984;Troike, 1981). Yet, most teachers fail to capitalize on this in school, and may even counteract the educational benefits of heritage languages by discouraging students from using their first language and by neglecting to foster natural conversations in a first or second language in the classroom.…”
Section: Engaging In Natural Conversationsmentioning
confidence: 99%
“…Evidence was also found suggesting that better vocabulary knowledge produces better oral performance in terms of all the aspects examined -fluency, accuracy, complexity, and global impression. This adds oral performance to the list of areas in second language learning that appear to be influenced by vocabulary knowledge, which as noted earlier includes both reading comprehension [14,15] and academic performance [16,17]. The following sections discuss these findings further, exploring some of the possible reasons for the relationships found (as well as those not found) in this study, and the implications of the findings towards more effective second language learning and instruction.…”
Section: Discussionmentioning
confidence: 83%
“…Where academic achievement is concerned, SavilleTroike [16] found that vocabulary knowledge was a predictor of academic achievement of non-native-English-speaking children, aged 6 to 12 years old, mainstreamed in Englishmedium classes. More recently, Loewen and Ellis [17] reported similar results for ESL university students.…”
Section: The Importance Of Vocabulary Knowledgementioning
confidence: 99%
“…Saville-Troike, Bridgeman and Carlson, Horowitz, and Ostler for example, used surveys to assess what types of academic activities students were performing at the college level. 3 Other studies, (Christison and Krahnke, Leki and Carson) have examined the students' own perceptions of their academic needs. 4 Other studies (Currie, Shuck) have looked specifically at the needs for writing classes.…”
Section: Academic Literacy Skillsmentioning
confidence: 99%